Hydrodynamic Studies in Slurry Bubble Columns: Experimental and Numerical Study. Issue 7 (25th April 2013) - Rabha, Swapna; Schubert, Markus; Hampel, Uwe; Grünewald, Marcus; Lausch, Hans‐Rolf; Schlüter, Michael
Abstract To overcome the current difficulties in designing a slurry bubble column (SBC) reactor with respect to the effect of particle properties, the influence of solid concentration (Cs) on the hydrodynamics of a SBC was studied experimentally using ultrafast electron beam X‐ray tomography. The real time gas flow structure, average bubble diameter and average gas holdup as a function of the superficial gas velocity and Cs have been reported. Corresponding three‐phase simulations were also performed using the Euler‐Euler multi‐fluid model implemented in CFX 14. The bubble size distribution was calculated using the MUSIG model. The predicted gas holdup and bubble size distribution also show dependence on UG and Cs and agree well with the measurements.